Effects of simulated limb length discrepancy on the amount of pelvic movement across different height groups - Wei Siong, Chua (2015)

(untitled)
Introduction and objectives: Limb length discrepancy causes pelvic tilt and excessive pelvic movement which subsequently change the biomechanics of hip and spine. We conducted the study to determine the effects of simulated limb length discrepancies on pelvic movement throughout the gait cycle in different height groups. It also investigated the amount of longer limb knee flexion as a form of compensation to simulated limb length discrepancy Methodology: This is a cross sectional study of 30 normal volunteers, with 10 each in height groups of 130,150 and 170 cm. They were made to walk without shoe raise followed by 1, 2, and 3 cm shoe raise on one side to simulate leg-length discrepancy. The amount of sagittal and coronal pelvic movement throughout the gait cycle was recorded by 3D cameras via reflective markers placed on bony pelvic and lower limb landmarks. The amount of pelvic motion was taken as the difference from the peak and the trough of the pelvic angle graph. The amount of maximum knee flexion was also assessed in the similar way. The analysis within and between groups were analysed using repeated measure analysis of variance. Results: There were no significant differences in the mean of sagittal (P-0.67) and coronal (P-0.38) pelvic movement among the individuals with simulated limb length discrepancy between 1 cm to 3 cm . Similar findings were found on volunteers with height between 130 to 170 cm with a range of simulated limb length discrepancies between 1.9% to 7.7% of the lower limb. Mean amount of knee flexion (P-0.93) throughout the gait cycle was no different between all the studied height groups. Conclusion: Various simulated limb length discrepancy of 7.7% or less of the lower limb length did not cause a significant different in amount of coronal and sagittal pelvic motion in subjects between 130 to 170 cm height. Inconsistent amount of knee flexion as compensation of different simulated limb length discrepancies indicate that other parts also contribute to the compensation